PERAN BANK SYARIAH DALAM PEMBIAYAAN INDUSTRI HALAL: ANALISIS PELUANG DAN TANTANGAN - Alya, Alya; Andi Hunafa Iskandar; Nanda Dwi Nopianti; Kamaruddin, Kamaruddin (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study seeks to explore the involvement of Bank Syariah Indonesia (BSI) in the advancement of the halal industry in Indonesia, especially with a focus on BSI's branch located in Makassar City. Using qualitative research methods with a descriptive approach, this study uses various sources and data collection techniques, including observation, interviews, and documentation. The growth of the halal industry is inseparable from the important role of financial institutions, especially Islamic banks. This study aims to measure the contribution of Islamic banks in financing the halal industry. By analyzing the various financing schemes offered, this study will identify the factors that affect the participation rate of Islamic banks in the halal industry. In addition, this study will also examine the impact of Islamic bank financing on the performance of halal companies.